Analisis Pengaruh Penerapan PSAK No.46 Terhadap Laporan Laba Rugi Pada Lima Perusahan Yang Terdaftar Di BEI - Kusmala, Abdilla Rahmania; Hastoni, Hastoni (Institut Bisnis dan Informatika Kesatuan, 2014)
The purpose of this research is to examine if PSAK NO. 46 is applied by these following companies: the PT Astra International Tbk, PT Mustika Ratu Tbk, PT Indah Maju Tbk, PT Gudang Garam Tbk, and PT Aneka Tambang, Tbk and how its application influences the companies ' income statements. The data of the income statements were obtained from Pojok Bursa Efek Indonesia at STIE Kesatuan. The results showed that in the application of PSAK NO. 46 will develop assets and deferred tax liabilities interest arising due to temporary differences. The application of PSAK NO. 46 give rise to a difference between the burden of income tax with income tax debt resulting from the existence of differences in recognition of taxdeferred interest assets, which is set to PSAK NO. 46. Keywords : PSAK 46, Deferred Tax Assets, Income Tax Expenses